Toward an understanding of optimal development environments within elite English soccer academies - Mills, M.; Butt, J.; Maynard, I.; Harwood, C. (The Sport Psychologist, 2014)
This study examined the factors perceived by successful coaches to underpin optimal development environments within elite English soccer academies. A semistructured interview guide was developed to interview 10 expert coaches about the environments they create for players at a key stage in their development. The interviews were transcribed verbatim and inductively content analyzed. The results identified a wide range of factors resulting in a conceptual framework that explained how these factors interact to underpin an optimal environment. Subcomponents of this framework included organizational core (e.g., advocate a player-driven ideology), adaptability (e.g., embrace novel ideas & approaches), player welfare (e.g., understand players` world-view), key stakeholder relationships (e.g., build trust with parents), involvement (e.g., encourage players` ideas/feedback), and achievement oriented (e.g., establish an explicit pathway to senior level). Collectively, the findings highlight the importance of establishing strong, dynamic, organizational cultures at elite youth soccer academies. Ways that academies might be helped to establish such environments are discussed.